2008
DOI: 10.1103/physreve.77.026210
|View full text |Cite
|
Sign up to set email alerts
|

Energy enhancement and chaos control in microelectromechanical systems

Abstract: For a resonator in an electrostatic microelectromechanical system (MEMS), nonlinear coupling between applied electrostatic force and the mechanical motion of the resonator can lead to chaotic oscillations. Better performance of the device can be achieved when the oscillations are periodic with large amplitude. We investigate the nonlinear dynamics of a system of deformable doubly clamped beam, which is the core in many MEMS resonators, and propose a control strategy to convert chaos into periodic motions with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 28 publications
1
58
0
Order By: Relevance
“…In practice, Park showed that Eq. (3) is an excellent approximation for systems with many degrees of freedom, 20 and we show that inclusion of higher orders is not necessary for the three systems studied here with our onthe-fly weight updating. We also remark that we can use the original recursion formulae 6, 12, 13 instead of Eq.…”
mentioning
confidence: 99%
“…In practice, Park showed that Eq. (3) is an excellent approximation for systems with many degrees of freedom, 20 and we show that inclusion of higher orders is not necessary for the three systems studied here with our onthe-fly weight updating. We also remark that we can use the original recursion formulae 6, 12, 13 instead of Eq.…”
mentioning
confidence: 99%
“…In more recent years, considerable attention has been paid to the application of ST to biomolecular simulations [36][37][38] due to its better scaling property with system size and superior acceptance ratio for temperature transitions. Several comparison studies [39][40][41] revealed that ST with a properly chosen temperature weight exhibits faster diffusion in temperature space and a better sampling efficiency in comparison to the tREM. Combinations of the ST and other enhanced sampling methods have further explored this synergistic advantage.…”
Section: Introductionmentioning
confidence: 99%
“…Chaos can be desirable in some applications such as micro-fluidic mixtures and communications to encrypt signals [10]. However, in most cases, it is unwelcome and can result harmful consequences.…”
Section: Introductionmentioning
confidence: 99%